The Oxford Group Movement between the Wars - Bebbington, David (Studies in church history, 1986)
IN July 1935 Lady Margaret Hall, Oxford, was the setting for an international gathering that attracted thousands of the eminent and the curious, many of them churchmen. ‘Similar ‘house-parties’ had been held every year since 1930. At free periods during the day, recalled Beverley Nichols, an enthusiast on his first visit, ‘the High Street seemed afire with shining faces’; last thing at night attenders could enjoy a ‘lemonade and biscuit’ party in the Toynbee Room. The main business, however, consisted of sessions where those present listened to testimonies of changed lives, of how people had ‘surrendered’ and were now ‘all out for God’. These were the main annual meetings of the Oxford Group.